2017
DOI: 10.1080/09513590.2017.1370645
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of recurrent lower urinary tract infections in postmenopausal women with genitourinary syndrome: outcome after 6 months of treatment with ospemifene

Abstract: Aim of this study was to evaluate the efficacy of ospemifene in the prevention of recurrent lower urinary tract infections in postmenopausal women with vulvovaginal atrophy. The study have a retrospective design. Thirty-nine patients were enrolled. Patients underwent clinical examination and urine culture. The urinary symptoms and the quality of life were evaluated with UTISA score, PUF and SF-36 questionnaires before and after treatment. All 39 patients received ospemifene 60 mg one tablet/daily for 6 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Either the original English or the translated versions in different languages (Uzbek, Russian, Italian, Chinese) of the UTISA were used as primary or additional symptom-assessment tools in studies [47][48][49][50][51]. Although the authors of the original UTISA did not aim to establish a cutoff value to differentiate between AC and other conditions, Chang et al [51] revealed such a cutoff value using the total summary score in a translated and validated Chinese version of the UTISA, using receiver operating characteristic-curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Either the original English or the translated versions in different languages (Uzbek, Russian, Italian, Chinese) of the UTISA were used as primary or additional symptom-assessment tools in studies [47][48][49][50][51]. Although the authors of the original UTISA did not aim to establish a cutoff value to differentiate between AC and other conditions, Chang et al [51] revealed such a cutoff value using the total summary score in a translated and validated Chinese version of the UTISA, using receiver operating characteristic-curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is intended to be used to treat moderate-to-severe dyspareunia due to vulvovaginal atrophy and it has no major adverse effects on the breast, bone or cardiovascular systems of patients [44]. Hence, ospemifene could be a promising new non-antibiotic option for UTI prevention in postmenopausal patients, especially in those with additional vulvovaginal atrophy [45]. However, no valid data on its possible preventive effect are available at present.…”
Section: Resultsmentioning
confidence: 99%
“…There is clinical trial evidence to show that ospemifene may prevent recurrent UTIs in postmenopausal women. 15 …”
Section: Clinical Overviewmentioning
confidence: 99%